Food Dependency and Global Food Crisis. Issue 2 (3rd April 2019) - Xu, Zhun
ABSTRACT: A key feature of the contemporary global economy is the unevenness of food production and trade. The problem of food dependency and the system's lack of capacity to accommodate global demand continue to haunt the global food trade and capitalism in general. This paper shows that the global food trade emerged as a solution to the problem of food in capitalist development; however, this solution so far has been clearly limited in its scope and capacity. By exploring the three major global food crises since the mid-nineteenth century, I trace the historical forces behind the crises and the restructuring of the global food trade and production. Finally, I discuss the future of food in global capitalism and the ways of better feeding the world population, especially those in the third world.